Chemical and Morphological Composition of Norway Spruce Wood (Picea abies, L.) in the Dependence of Its Storage - Čabalová, Iveta; Bélik, Michal; Kučerová, Viera; Jurczyková, Tereza (Polymers, 2021)
Chemical composition and morphological properties of Norway spruce wood and bark were evaluated. The extractives, cellulose, hemicelluloses, and lignin contents were determined by wet chemistry methods. The dimensional characteristics of the fibers (length and width) were measured by Fiber Tester. The results of the chemical analysis of wood and bark show the differences between the trunk and top part, as well as in the different heights of the trunk and in the cross section of the trunk. The biggest changes were noticed between bark trunk and bark top. The bark top contains 10% more of extractives and 9.5% less of lignin. Fiber length and width depends on the part of the tree, while the average of these properties are larger depending on height. Both wood and bark from the trunk contains a higher content of fines (fibers <0.3 mm) and less content of longer fibers (>0.5 mm) compared to the top. During storage, it reached a decrease of extractives mainly in bark. Wood from the trunk retained very good durability in terms of chemical composition during the storage. In view of the morphological characteristics, it occurred to decrease both average fibers length and width in wood and bark.
Keywords: time of storage; spruce wood; cellulose; fiber characteristics; lignin; hemicelluloses; extractives